MELILITIC AND MONTICELLITE-BEARING ROCKS OF THE KRESTOVSKAYA INTRUSION (NORTHERN SIBERIAN PLATFORM) AND THEIR GENESIS - Panina L.I.; Sazonov A.M.; Usol'tseva L.M. (My University, 2001)
The geologic structure of the Krestovskaya intrusion, discovered in 1996, is discussed. Petrographic characteristics of melilitic and monticellite-bearing rocks, their mineralogy and composition of minerals, including rare ones (kalsilite, combeite, rankinite, larnite, and djerfisherite), are reported. Studies of melt inclusions have shown that melilitic and monticellite-bearing rocks crystallized at the magmatic stage in the following sequence: perovskite (1250-1230°C) → melilite (1235-1160°C) → monticellite (1090-990°C). The melt during crystallization of perovskite was lowly siliceous (30-33 wt.% SiO2), depleted in Al2O3 (5-6wt.%) and MgO (6-8 wt.%), enriched in CaO (17-21 wt.%) and alkalies (totalling about 11 wt.% with predominance of K over Na), and contained 2-3% SO3 and, perhaps, some quantities of Cl and CO2, i. e., was alkaline-ultramafic, enriched in Ca, and had K-Na or even Na-K type of alkalinity. During crystallization of perovskite, liquid silicate-salt immiscibility manifested itself. Crystallization of melilite started from the same melt and proceeded under the conditions of ongoing two-phase liquid immiscibility with a drastically changing oxygen fugacity. During crystallization and fractionation of melilite, the contents of Si and Al in the melt strongly increased, the content of Fe sharply decreased, the amount of Na in the total of alkalies diminished and that of K grew, and the quantities of Ca and Mg remained the same. Subsequently the high content of K favored binding of Al-Si radicals into molecules of phlogopite and kalsilite and crystallization of djerfisherite under reducing conditions. The extremely high activity of Ca favored crystallization of rather rare calcium silicates, larnite and rankinite, and binding of the rest amount of Na into combeite and pectolite. The silicate-salt melt, spatially separated as a result of liquid immiscibility, was compositionally close to highly siliceous carbonatitic alkaline melt of Fort Portal in Uganda. It was responsible for autometasomatic transformation of olivine and pyroxene rocks, which resulted in monticellite and garnet at the magmatic stage. Among volatiles, CO2 and H2O were predominant in silicate-salt melts, while CO was present in minor amount.